Sistem Informasi Pengambilan Keputusan Penerima Rehab Rumah Menggunakan Metode Weighted Sum Model (WSM) Pada Desa Bira Lhok Kecamatan Montasik - Sadakta Shopalazuli; Baihaqi Baihaqi; Erdiwansyah Erdiwansyah (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
The house renovation program provided by the Aceh Besar regional government, especially in Gampong Bira Lhok, Montasik District, is an assistance program for the welfare of villagers whose housing conditions are far from livable. The problem faced by the Gampong government in the decision system for recipients of house renovation assistance at this time is that it still uses the decision system of deliberations between the Gampong apparatus and the Village Head so that it takes time to make decisions. Therefore, it is necessary to have a Decision Support System (SPK) to determine the acceptance of the house rehab program for residents with livable housing conditions based on computer information systems. This final project research aims to build a decision-making information system for home rehabilitation recipients using the Weighted Sum Model (WSM) method in Bira Lhok Village, Montasik District. The system development method used is the SDLC (Software Development Life Cycle) method using PHP and MySQL programming. The final project research resulted in a decision making information system for home rehabilitation recipients using the web-based Weighted Sum Model (WSM) with a factor weighting form interface, a form for prospective beneficiaries, a form for income criteria, assets, food and buildings, as well as a report on the assessment list of prospective recipients of rehabilitation assistance. House. Based on the results of the system that was built, the presence of an information system for decision making for home rehabilitation recipients using the Weighted Sum Model (WSM) method has made it easier for the Gampong Bira Lhok government to make decisions for recipients of home rehabilitation assistance quickly.